Radiation-induced non-cancer risks in interventional cardiology: Optimisation of procedures and staff and patient dose reduction - Sun, Z.; AbAziz, A.; Md Yusof, A. (Hindawi Publishing Corporation, 2013)
Concerns about ionizing radiation during interventional cardiology have been increased in recent years as a result of rapid growth in interventional procedure volumes and the high radiation doses associated with some procedures. Non-cancer radiation risks to cardiologists and medical staff in terms of radiation-induced cataracts, and skin injuries for patients appear clear potential consequences of interventional cardiology procedures, while radiation-induced potential risk of developing cardiovascular effects remain less clear. This paper provides an overview of the evidence-based reviews of concerns about non-cancer risks of radiation exposure in interventional cardiology. Strategies commonly undertaken to reduce radiation doses to both medical staff and patients during interventional cardiology procedures are discussed; optimisation of interventional cardiology procedures is highlighted.